1989
DOI: 10.1182/blood.v73.4.945.bloodjournal734945
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human interleukin-3 (multi-CSF) is restricted to human lymphocytes and T-cell tumor lines

Abstract: While the cellular sources for granulocyte-macrophage colony- stimulating factor (GM-CSF) are known to be widely distributed among several cell types, interleukin-3 (IL-3) gene expression has been demonstrated in only certain T-cell clones and in blood mononuclear cells stimulated with phytohemagglutinin (PHA) and phorbol-myristate- acetate (PMA). To determine which blood cells were responsible for this expression, we fractionated PHA/PMA-stimulated mononuclear cells and identified T lymphocytes as the source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…Ferrer et al [24] demonstrated that pre-incubating basophils with IL-3 increased the amount of histamine release, induced by sera from chronic urticaria patients. It is of importance to notice that IL-3 gene expression has been demonstrated in activated T cells [25]. The sources of MMP-9 were not identified in this study.…”
Section: Discussionmentioning
confidence: 63%
“…Ferrer et al [24] demonstrated that pre-incubating basophils with IL-3 increased the amount of histamine release, induced by sera from chronic urticaria patients. It is of importance to notice that IL-3 gene expression has been demonstrated in activated T cells [25]. The sources of MMP-9 were not identified in this study.…”
Section: Discussionmentioning
confidence: 63%
“…As CD2 mRNA was also detected it can be surmised that T cells are present in the adherent stroma layer (Niemeyer et a!, 1989) and it raises the question of whether IL-3 production is exclusive to this subpopulation within the stroma. Ongoing studies employing single-cell identification techniques such as in situ hybridization with RNA probes, wili establish the contribution of specific stroma cell types to 1L-3 production.…”
Section: Discussionmentioning
confidence: 99%
“…This was further supported by the observation that stromal cells remained of host origin following marrow transplantation, even in those patients cured of their disease (Simmons et al, 1987). However, more recent studies suggest that there are non-stromal components of the microenvironment, i.e., monocytes and lymphocytes, which play critical roles in affecting stromal cell function (Vellenga et al, 1988;Niemeyer et al, 1989). Acquired defects within these cell compartments could interfere with the function of the microenvironment, causing marrow failure and resulting in pancytopenia.…”
Section: Discussionmentioning
confidence: 99%